Visual propaganda at a crossroads: new techniques at Iran's Vali Asr billboard. Issue 4 (20th October 2021) - Schwartz, Kevin L.; Gölz, Olmo
Abstract : Located at one of Iran's busiest intersections, the Vali Asr billboard has been a key venue for projecting and promoting the regime messaging of the Islamic Republic since 2015. With its unique ability to frequently change its images, unlike the more traditional painted murals populating Iran's urban landscape, the Vali Asr billboard has the capacity to convey a wide-range of regime messages tailor-made for a variety of domestic and international events, whether foreseen or unforeseen, from national holidays to the outbreak of Covid-19. This article assesses how the Vali Asr billboard's unique features and design style allow it to present a mix of 'hard' and 'soft' propaganda and succeed in attracting public engagement with its images. Through a close analysis of the assassination of Islamic Revolutionary Guard Corps (IRGC) commander Qassem Suleimani (d. 2020), a series of murals unveiled during the holy month of Muharram in 2020, and a controversy around the 2018 World Cup, the article argues that the Vali Asr billboard is a unique communicative medium and potent tool for regime cultural producers in Iran's twenty-first century media landscape.